Navigating Between Stealth Advocacy and Unconscious Dogmatism: The Challenge of Researching the Norms, Politics and Power of Global Health - Gorik Ooms (Kerman University of Medical Sciences, 2015)
Global health research is essentially a normative undertaking: we use it to propose policies that ought to be implemented. To arrive at a normative conclusion in a logical way requires at least one normative premise, one that cannot be derived from empirical evidence alone. But there is no widely accepted normative premise for global health, and the actors with the power to set policies may use a different normative premise than the scholars that propose policies - which may explain the 'implementation gap' in global health. If global health scholars shy away from the normative debate - because it requires normative premises that cannot be derived from empirical evidence alone - they not only mislead each other, they also prevent and stymie debate on the role of the powerhouses of global health, their normative premises, and the rights and wrongs of these premises. The humanities and social sciences are better equipped - and less reluctant - to approach the normative debate in a scientifically valid manner, and ought to be better integrated in the interdisciplinary research that global health research is, or should be.